STRATIGRAPHY OF THE LOWER OLIGOCENE NUMMULITIC LIMESTONES, NORTH OF SONQOR (NW IRAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
The lower Oligocene hyaline and porcellaneous larger foraminifera of a carbonate platform setting, north of Sonqor, were studied for high-resolution biostratigraphy in the context of European standard zonation (Shallow Benthic Zones). According to the geological map of Kermanshah, these beds were previously ascribed to the Miocene. The identified larger foraminifera include Nummulites fichteli Michelotti, Nummulites vascus Joly & Leymerie, Operculina complanata (Defrance), Asterigerina rotula (Kaufmann), Planorbulina bronnimanni Bignot & Decrouez, Discogypsina discus (Goës), Gypsina mastelensis Bursch, Halkyardia maxima Cimerman, Stomatorbina concentrica (Parker & Jones), Praerhapydionina delicata Henson, Penarchaias glynnjonesi (Henson), Austrotrillina aff. paucialveolata Grimsdale, and Haddonia heissigi Hagn, associated with the coralline alga Subterraniphyllum thomasii Elliott. The foraminiferal association characterises the SBZ 21 Zone (early Rupelian).